A study on effect of different inter-pregnancy intervals on perinatal outcomes - Bajrachraya, Sumana (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: Both short and long inter-pregnancy intervals have been found to increase various adverse perinatal outcomes such as low birth weight, preterm delivery, and small for gestational age, still birth and neonatal death. This proposed study was endeavor to find out impact of different inter-pregnancy interval on perinatal outcome like preterm birth, low birth weight, perinatal death in second gravida women of age group 18 – 35 yearsMethods: This is a cross-sectional study conducted in Patan Hospital, Lalitpur in 2064 B.S. from 1st of Magh to 31st Falgun. Total 84 Patients included in the study were the women of second gravida of age group 18 – 35 years. The study population was divided into three inter-pregnancy interval < 18, 18 – 59 & >59 months. All the women of second gravida who fitted in the study were interviewed with the questionnaire after taking an informed consent.Results: Among the total 84 women who were included in the study, maximum number (57.1%) of women were of IPI >59 months. In women with IPI 59 months, 33.4% & 16.7% of women had preterm delivery respectively. All women with IPI 18-59 months had termed delivery. (P value=0.007). Among women with IPI 59 months, 50.05% & 25% woman had delivered low birth weight babies respectively. And in a group of IPI 18- 59, only 16.7% of women delivered low birth weight babies. (p value=0.272). There was only one perinatal death in the group of IPI > 59 months. In comparison of APGAR score at 5 minutes of delivery with IPI, all babies were found to have APGAR score 7 - 10.Conclusion: There is an increased risk of preterm & low birth weight babies in women with IPI < 18 months and > 59 months compared to women with IPI 18 – 59 months